Retroperitoneal cystic lymphangioma coexisting with a uterine fibroid in a 42-year-old woman: A case report - Fatima El Hassouni; Sofia Mchichou; Samia Sassi; Najat Lamalmi; Samir Bargach; Mounia Yousfi malki; Siham El Haddad; Kenza Berrada (Elsevier, 2024)
Lymphangiomas are rare benign neoplasms traditionally thought to result from congenital lymphatic channel malformations, though they may also be associated with other conditions. Retroperitoneal lymphangiomas account for 1% of all lymphangiomas, and fewer than 200 cases have been reported. A 42-year-old woman was admitted with symptoms of abdominal pain and distension. A computerized tomography (CT) scan showed an abdomino-pelvic mass and a giant uterine myoma. The patient underwent explorative laparotomy and the whole cyst mass was removed along with the uterine myoma. Cystic lymphangiomas are often misdiagnosed because of the vague symptoms and the absence of obvious etiology. A provisional diagnosis can be made with CT but histological examination confirms the diagnosis. Cystic lymphangioma should be included in the differential diagnosis of an ovarian cystic mass. Complete resection can be curative.